Style of Women Leadership in Developing Community Organization: Case Study on Moeldoko Center - Suherman, Trisya; Ranti, Benny; Suharyono, Suharyono; Pakpahan, Marisi (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study explores women’s leadership in community-based organizations through a case study of the Moeldoko Center. Based on the author's experience as Chairwoman, it highlights the challenges women face in patriarchal settings. Using PESTEL analysis and an ethnographic approach, the study reveals that from 2021–2024, collaborative and transformational leadership styles dominated. These styles fostered synergy, open communication, and strategic innovation—such as alternative food programs, legal aid, and Moel Coffee. Women’s leadership emerged as a driver of inclusive and sustainable transformation. The research enriches leadership theory with a gender perspective and offers practical insights for similar organizations in Indonesia.